Modeling the relationship between perceived service quality, tourist satisfaction, and tourists’ behavioral intentions amid COVID-19 pandemic: Evidence of yoga tourists’ perspectives - Abdou, Ahmed Hassan; Mohamed, Shaimaa Abo Khanger; Khalil, Ayman Ahmed Farag; Albakhit, Azzam Ibrahem; Alarjani, Ali Jukhayer Nader (Frontiers in Psychology, 2022)
Purpose: This study aims to investigate the impact of perceived service quality (PSQ) on tourist satisfaction and behavioral intentions and explore the potential mediating role of tourist satisfaction in the relationship between service quality and behavioral intentions in the yoga tourism context during the COVID-19 pandemic. Further, this is to examine to what extent yoga tourist satisfaction directly affects their behavioral intentions. Design/methodology/approach: Based on a review of literature, the study proposes a conceptual model to test four hypothesized relationships among the constructs of perceived service quality, tourist satisfaction, and behavioral intentions. Data was collected by using a self-administrated questionnaire that was developed and directed to a convivence sample of yoga tourists (380 forms). Structural Equation Modeling (SEM) was employed to determine the relationship between study constructs. Findings: The results of SEM illustrated that all the hypothesized relationships are supported. The findings confirm that yoga tourists’ behavioral intentions are significantly affected directly and indirectly (through tourist satisfaction) by perceived service quality. Additionally, tourist satisfaction significantly partially mediates the relationship between PSQ and tourists’ behavioral intentions. Research limitations: The subject of this study was yoga tourists staying in yoga retreats/studios in Egyptian destinations (South Sinai Governorate). Future research may focus on other geographical destinations and other influential variables of yoga tourists’ satisfaction and behavioral intentions should be investigated. Practical implications: For improving tourists’ satisfaction and behavioral intentions, yoga service providers should take care by giving tourists personalized attention, and understanding, fulfilling their specific needs. Health and hygiene practices must be considered during the COVID-19 pandemic. Originality/value: This study is perhaps the first empirical study that examines the relationship between PSQ and tourists’ satisfaction and behavioral intentions in the yoga tourism context. A new integrated conceptual model that combined three service quality dimensions, namely, tangibles, intangibles as well as health and hygiene was developed and validated.